The Effect of Product Quality and Store Atmosphere on Puchase Decisions mediated By Purchase Intention as Intervening Variable (Study at Café Ma’Ani Rengat) - Rianti, Tranita; Taufiqurrahman, Taufiqurrahman; Firli Musfar, Tengku (Dinasti Publisher, 2023)
This study aims to determine the effect of product quality and store atmosphere on purchase decisions mediated by purchase intention as intervening variable. The type of research conducted is quantitative research with primary data using questionnaire as an instrument to prove the result of the research. The population in this study is all the customers of Café Ma’Ani Rengat. To test the hypothesis in this study is using path analysis with Statistical Program for Social Science (SPSS) 20. The sampling method used a non-probability sampling method with purposive sampling technique (102 respondents). The result of the study indicate that product quality and store atmosphere have a significant ang positive effect on purchase intention. Product quality and store atmosphere have a positive and not significant effect on purchase decision. Product quality and store atmosphere have a positive significant effect towards purchase decision through purchase intention. And purchase intention has a positive significant effect towards purchase decision.